Immersive Reconstruction of the Sriwijaya Kingdom: Developing a Metaverse-Based Learning Environment for Cultural Preservation - Yudi Pratama; Neni Wahyuningtyas; Bayu Kurniawan (Universitas Hamzanwadi, 2026)
This research's purpose is to create and subsequently confirm the efficacy of a virtual world-based learning experience representing a bygone civilization, specifically the Srivijaya Empire, as part of a project to digitally preserve and teach about historic events. The research used research and development techniques based on the 4-D model which includes a definition, design, development, and validation phase. The final products being developed include virtual reality (VR), augmented reality (AR) and other forms of virtual representations such as 3D models, and will also include an immersive video format with 360° views which can be viewed via YouTube in order to make them more widely available as well as accessible to more people. The needs analysis showed there were problems with the way history has been traditionally taught, especially when trying to provide local historical heritage in terms of what happened and how it happened within the context of that particular location. The design phase focused on creating a narrative reconstruction that depicts the maritime trading network and socio/cultural/religious life that existed during the time of the Srivijaya Kingdom, based on both historiography and archaeological evidence. During the development phase, there was a validation process for the two media specialists and the two content specialists who validated the content by completing a limited practicality test with sixty students. Validation results were very positive in each tested area: visual design, navigation systems; use of technology, and historical accuracy (scores averaged above 4.5 on a 5-level Likert scale). Students perceived the research materials as highly practical, especially regarding usability and their ability to increase their historical contextual knowledge. At present this research represents an initial phase limited to validation and practicality testing, and thus has not provided an assessment of learning effectiveness through experimental comparison. This research creates a prototype for immersive digital heritage learning, utilizing historical reconstruction based on metaverse principles and combining these elements and theories for instructional design. Therefore, the results will create a framework that can serve as a basis for further development toward supporting the preservation of digital cultural heritage through educational systems.